Penafsiran Restriktif Atas Pasal 28 Ayat (2) UU ITE - Aulia Anastasya Putri Permana; Shafarina Intan Khomsah (Fakultas Hukum Universitas Surabaya, 2021)
The purpose this paper to interpret the content of a law, namely is the regulation regarding the ethics of delivering criticism through social media as regulated in the ITE Law. Article 28 Paragraph (2) of the UU ITE is considered to limit constitusional rights of opinin and expression. The explanation of Article 28 Paragraph (2) transctional and electronic information law is gives different interpretations as fragments of paragraph “spreading informaton” and “causing a sense of hatred/hostility”. This considered an unclear limitation on the right to freedom opinion and expression on social media. The problem in study is how to interpret the restrictive and application the law solving problem of hate speech on social media. The method used in this study, normative juridical approach, is the carried out based on the main legal material by examining theories, concepts, legal principles and laws regulations. It can be concluded in Indonesia a legal state where every action citizens is regulated in laws, the regulatin of submitting criticism through social media which is regulated in Law no. 11 of 2008 UU ITE. The Article 28 Paragraph (2) transactional and electronic information law, gives rise to the vage normen (blurred norms). It is can be abused silencing freedom of opinion and even becoming a political weapon. In the application of this law, it is indicated that there is duplication of criminal acts which are actually vulnerable to legal uncertainty so that it has the potential to cause turmoil in society.